Testing in artificial sweat – Is less more? Comparison of metal release in two different artificial sweat solutions - Midander, Klara; Julander, Anneli; Kettelarij, Jolinde; Lidén, Carola (Regulatory toxicology and pharmacology, 2016)
Metal release from materials immersed in artificial sweat can function as a measure of potential skin exposure. Several artificial sweat models exist that, to various degree, mimic realistic conditions. Study objective was to evaluate metal release from previously examined and well characterized materials in two different artificial sweat solutions; a comprehensive sweat model intended for use within research, based on the composition of human sweat; and the artificial sweat, EN1811, intended for testing compliance with the nickel restriction in REACH. The aim was to better understand whether there are advantages using either of the sweat solutions in bio-elution testing of materials. Metal release in two different artificial sweat solutions was compared for discs of a white gold alloy and two hard metals, and a rock drilling insert of tungsten carbide at 1 h, 24 h, 1 week and 1 month. The released amount of metal was analysed by means of inductively coupled plasma mass spectrometry. Similar levels of released metals were measured from test materials in the two different artificial sweat solutions. For purposes in relation to legislations, it was concluded that a metal release test using a simple artificial sweat composition may provide results that sufficiently indicate the degree of metal release at skin contact. •Metal release in artificial sweat indicates potential skin exposure.•Different artificial sweat models mimic realistic conditions, to various degree.•Metal release from test materials in different artificial sweat solutions was similar.•Testing in simple artificial sweat may sufficiently indicate the metal release at skin contact.